Exome Sequencing Identifies the Extremely Rare ITGAV and FN1 Variants in Early Onset Inflammatory Bowel Disease Patients - Al-Numan, Huda Husain; Jan, Rana Mohammed; Al-Saud, Najla bint Saud; Rashidi, Omran M.; Alrayes, Nuha Mohammad; Alsufyani, Hadeel A.; Mujalli, Abdulrahman; Shaik, Noor Ahmad; Mosli, Mahmoud Hisham; Elango, Ramu; Saadah, Omar I.; Banaganapalli, Babajan (Frontiers in Pediatrics, 2022)
Background: Molecular diagnosis of pediatric onset inflammatory bowel disease (IBD) is very important for adopting suitable treatment strategies. Owing to the sparse data available, this study aims to discover molecular basis of early onset IBD in Arab families. Methods: A consanguineous Arab family with monozygotic twins presenting early onset IBD was screened by whole exome sequencing (WES). The variants functional characterization was performed by a series of systems biology assays. The IBD variant was further screened in 100 in-house whole exome data to ensure its rare prevalence in the population. Results: Genetic screening has identified the digenic inheritance segregation of a novel ITGAV (G58V) and extremely rare FN1 (G313V) variants in IBD twins displaying autosomal recessive mode of inheritance. Findings from pathogenicity predictions, stability and molecular dynamics have confirmed the deleterious nature of both variants on structural features of the proteins. Functional biology data suggested that both genes show abundant expression in gastrointestinal tract and immune organs, involved in immune cell restriction, regulation of different immune related pathways and are predicted to be tractable by small molecules, PROTAC and antibodies. Data from knockout mice models for ITGAV gene has revealed the dysregulated expression of this gene impacts intestinal immune homeostasis. The defective ITGAV and FN1 involved in integrin pathway are likely to induce intestinal inflammation by disturbing immune homeostasis. Absence of these variants was confirmed by variant analysis in 100 Arab control cases. Conclusions: Our findings provide novel insights into the molecular etiology of pediatric onset IBD and may likely pave way in developing novel medicine.